Cryo-electron microscopy instrumentation and techniques for life sciences and materials science. (December 2019) - Williams, Robert E.A.; McComb, David W.; Subramaniam, Sriram
Abstract: Abstract : In this article, we review some of the recent developments in instrumentation and methods that have led to the rise of cryo-electron microscopy (cryo-EM) in the life sciences community, and consider how researchers in the materials community might benefit from these advances. Transmission electron microscopy (TEM) is compared with scanning transmission electron microscopy (STEM) for cryogenic imaging in both biological and materials science applications. We discuss the developments in detector technologies that have in part powered the development of cryo-EM and anticipate exciting areas for productive overlap between life science and materials science cryo-EM applications.